Case report: Efficacy of lutetium-177 oxodotreotide for neuroendocrine tumor with central nervous system metastases - Okwundu, Nwanneka; Weil, Christopher R.; Soares, Heloisa P.; Fine, Gabriel C.; Cannon, Donald M. (Frontiers in Nuclear Medicine, 2023)
Neuroendocrine tumors (NETs) rarely metastasize to the brain. However, when they occur, NET brain metastases are associated with a poor prognosis. Due to their low incidence, NET brain metastases are poorly studied, with few data to guide a consensus for management. Prior reports have documented treatment with chemotherapy, resection, whole brain radiation therapy, and stereotactic radiosurgery, all with low rates of survival. We present a case of a patient with type 3 well-differentiated gastric NET with widespread metastatic disease, including central nervous system lesions in the pineal gland and left cerebellopontine angle (CPA), which were avid on 68Ga-dotatate positron emission tomography. The patient received four doses of 200 mCi (7.4 GBq) lutetium-177 oxodotreotide (177Lu-dotatate) administered every 8 weeks over the course of 6 months. The treatments provided local control of the pineal and CPA lesions for 23 months until the development of diffuse leptomeningeal progression that necessitated further therapies. 177Lu-dotatate may be a viable treatment for local control of NET brain metastases. More studies are needed to validate its efficacy in this clinical scenario.